Early- and late -onset preeclampsia: an old disease, new ideas - Lacunza Paredes, Rommel Omar (2015)
Significant differences between preeclampsia manifestations before (early-onset) and after 34weeks (late-onset) raise the possibility that these are two different diseases. This hypothesisis strengthened based on genetic, epidemiological and placental differences. However, recentstudies show the possibility of temporal continuity between both clinical phenotypes. In thiscontext antiangiogenic phenomena and their relation with the fetus may be crucial in clarifyingthis unanswered question.Keywords: Early-onset preeclampsia, late-onset preeclampsia, antiangiogenic imbalance